Analysis of Technologies for the Development of Internet Based Business Applications - Velev, Dimitar (Research Papers, 2009)
The paper analyses the technological specifics for the development of Internet based business applications. The requirements for the development of such applications are presented, as well as the main problems. The main categories of Web based business applications are defined and the main features of each one of them are described. The potential users are acknowledged.The paper’s focuses on the individual software technologies for the development of Internet based business applications and detailed descriptions are presented for each one of them. The software technologies and languages of leading software companies in this field are analyzed. Certain attention is given to the use of open standards and solutions.A special attention is provided to the analysis of the technologies for the development of Internet based business applications with regard to the Web 2.0 concept. Not only the new peculiarities are pointed in this concept, but also its individual components for the enhancement of its functionality and expanding the sphere of Internet based business applications. Pending problems in connection with other technologies, supporting business models and processes in WWW, are mentioned.